In silico analysis of structural complex of HAESA receptor like kinase with PAMP IDA and SERk1 co-receptor - Alvy, Raghib Ishraq (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.